2022
DOI: 10.1109/tse.2020.3040935
|View full text |Cite
|
Sign up to set email alerts
|

A Wizard of Oz Study Simulating API Usage Dialogues With a Virtual Assistant

Abstract: Virtual Assistant technology is rapidly proliferating to improve productivity in a variety of tasks. While several virtual assistants for everyday tasks are well-known (e.g., Siri, Cortana, Alexa), assistants for specialty tasks such as software engineering are rarer. One key reason software engineering assistants are rare is that very few experimental datasets are available and suitable for training the AI that is the bedrock of current virtual assistants. In this paper, we present a set of Wizard of Oz exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…An example within Software Engineering research is Wood et al [14], which identified 26 dialogue act types for a hypothetical system to help programmers debug. This paper focuses on API search, and is based on the action space identified by Eberhart et al [15]. That paper presented a Wizard-of-Oz (WoZ) study in which programmers interacted with a hypothetical dialogue system for API usability.…”
Section: A Dialogue Actsmentioning
confidence: 99%
See 3 more Smart Citations
“…An example within Software Engineering research is Wood et al [14], which identified 26 dialogue act types for a hypothetical system to help programmers debug. This paper focuses on API search, and is based on the action space identified by Eberhart et al [15]. That paper presented a Wizard-of-Oz (WoZ) study in which programmers interacted with a hypothetical dialogue system for API usability.…”
Section: A Dialogue Actsmentioning
confidence: 99%
“…These actions enable users to search for API components by providing unstructured natural language queries, as well as specific keywords. Duala-Ekoko and Robillard [45], Sadowski et al [46], and Eberhart et al [15] have demonstrated that natural language queries play a more significant role in the API information-seeking process than e.g., signature-matching and faceted search. Furthermore, a broad range of techniques have been investigated supporting semantic search for APIs and source code [47], [48].…”
Section: A Action Spacementioning
confidence: 99%
See 2 more Smart Citations
“…A "basic" question is a question about a small detail of a method, such as "what are the parameters to the method convertWavToMp3?" We use basic question because: 1) Eberhart et al [7] found that programmers ask these questions about Java methods during actual programming tasks and isolated five types of these questions, and 2) the "basic" questions provide an excellent stepping-stone problem towards larger problems later. We built question and answer templates and paraphrases based on Eberhart et al's basic question types to construct a dataset for 1.56m Java methods.…”
Section: Introductionmentioning
confidence: 99%